LEARNERS IN THE EFL LEARNING LANDSCAPE OF 2022 - Immawan Iqbal Prasadana; Yohanes Gatot Sutapa Yuliana; Dwi Riyanti (Universitas PGRI Sumatera Barat, 2025)
Adult learners tend to have challenges in learning EFL, and these challenges are more apparent when the adult learners are faced with technologies in 2022. This paper aimed to find out the challenges encountered by adult learners in the EFL learning landscape of 2022 and what technologies are used by language teachers and researchers in order to counteract said challenges and assist the adult learners. The method used in this study is SLR (Systematic Literature Review). There are three journals focusing on challenges and three journals focusing on the solutions done by teachers and lecturers to help adult learners. These journals range from 2021 – 2022 (1 year) and were searched through Google Scholar, Research Gate, and Mendeley search engine. Hopefully the result of this research can be used by fellow language teachers in applying the proper teaching media when teaching adult learners and help them in facing their challenges.